Formulation and evaluation of simvastatin buccal film - Gamal M El-Maghraby, Mona M Abdelzaher (Journal of Applied Pharmaceutical Science, 2015)
The aim of this work was to develop and evaluate a buccal film for delivery of simvastatin. Buccal films containing carboxymethyl cellulose (CMC) with and without Polyvinylpyrrolidone (PVP) as polymers were prepared. Tween 80 was included with and without propylene glycol (PG) to modulate the characteristics of the films. The films were prepared by solvent casting with drug concentration being maintained at 2.5 mg/cm2. In absence of Tween and PG, the films were opaque due to precipitation of drug. PG reduced the swelling index and increased the thickness of the film due to shrinkage. Incorporation of PVP into the films increased the bioadhesion force and time. The rate of drug release depended on the composition of the film with the presence of PVP increasing the release efficiency compared to the corresponding PVP free films. Similarly, incorporation of PG increased the drug release efficiency. Thermal analysis indicated the presence of the drug in amorphous form or as a solid solution in the film components. The developed films are promising for buccal administration of simvastatin.
Keywords: Simvastatin, Buccal film, Solvent casting, Carboxymethyl cellulose, Polyvinylpyrrolidone.